Social position and chronic conditions across the life span and risk of stroke: a life course epidemiological analysis of 22 847 American adults in ages over 50. (11th December 2012) - Liu, Longjian; Xue, Fuzhong; Ma, Jixiang; Ma, Marshal; Long, Yong; Newschaffer, Craig J.
Abstract : Background: Evidence is limited on the impact of childhood socioeconomic status, adulthood socioeconomic status and chronic conditions on risk of incident stroke in later life. We aimed to examine these associations using data from a nationally representative sample of the Health and Retirement Study. Methods: Stroke‐free participants ( n  = 22 847) aged > 50 years in the Health and Retirement Study (1992–2008) were analyzed. Childhood and adulthood socioeconomic status were assessed using parental and participant's education attainments. Incident stroke was defined as self‐reported first incident stroke. Results: Of the study sample, 2298 subjects experienced first incident stroke (10·06%). Cox's regression models indicate that subjects with low childhood socioeconomic status had 1·36 times higher risk (95% confidence interval: 1·18–1·57) of first incident stroke than those with high childhood socioeconomic status. There was an 8% reduction of this association after adjustment for adulthood socioeconomic status. Adults with diabetes mellitus had the highest hazard ratio (1·91, 95% confidence interval: 1·63–2·23) for incident stroke, followed by heart disease (1·69, 1·48–1·93), and then hypertension (1·56, 1·40–1·75). Significant interaction effect of childhood socioeconomic status and diabetes mellitus, and combined effects of socioeconomic status and chronic conditions on risk of incident stroke were observed. Conclusions: Both low socioeconomic status in childhood and adulthood socioeconomic status predict the risk of stroke. There are significantly combined effects of socioeconomic status and chronic conditions on the risk of stroke. Improving socioeconomic status across the life span and aggressive control of chronic conditions may play pivotal roles in the prevention of stroke development.